Matching into Integrated Plastic Surgery: The Value of Research Fellowships. Issue 2 (February 2019) - Mehta, Karan; Sinno, Sammy; Thanik, Vishal; Weichman, Katie; Janis, Jeffrey E.; Patel, Ashit
Abstract : Background: Integrated plastic surgery residency applicants sometimes complete research fellowships before residency. The average productivity and the impact of these fellowships on subsequent application to residency are unknown. The purpose of this study was to provide objective data to better understand the utility and productivity of a research fellowship. Methods: A national survey was conducted in which integrated plastic surgery residency applicants from 2013 to 2016 were surveyed regarding their experiences with research fellowships. American Council of Academic Plastic Surgeons members were also surveyed to elicit their perspectives on the value of these fellowships. Results: Six hundred twenty-one integrated plastic surgery applicants from 2013 to 2016 were included in the study. Twenty-five percent of applicants participated in a research fellowship. Applicants who completed research fellowships were more likely to match into plastic surgery compared to those who did not (97 percent versus 81 percent, respectively; p < 0.05). Fellows were highly satisfied with their fellowship experience and produced an average of five publications and presentations per fellowship year. Sixty-three percent of research fellowships were performed to strengthen applications to categorical integrated plastic surgery residency. American Council of Academic Plastic Surgeons members considered three or four publications/presentations productive. Most do not recommend research fellowships to all medical students. Conclusions: Research fellowships can effectively prepare for categorical plastic surgery by improving publication and presentation experience. This is the first study to show that applicants who completed research fellowships were highly satisfied with their experience, accomplished higher than expected levels of productivity, and statistically significantly matched into an integrated plastic surgery residency more often than applicants without research fellowships.